Are We in the Movies Now ? - Johnson, Stacey (Cinémas, 1998)
ABSTRACTThe popularity of 8mm, home movie making swelled to notable proportions in the postwar period and throughout the 1950s, at which point 8mm movie cameras were in their widest, popular use in North American families. This paper explores the rise to ubiquity of postwar home movie production by tracing its cultural precedent to the mass-popularization of photography in the late-nineteenth century, and the ways in which a producing and consuming visual culture established itself in the family.